Pengembangan Kecerdasan Spiritual Siswa Melalui Pendidikan Agama Islam (PAI) di SDN Gajah 1 Ngoro Jombang - Amalia -; Hilyah Ashoumi; Umi Chaidaroh (Universitas KH. A. Wahab Hasbullah, 2018)
In this increasingly advanced age, globalization has influenced most of the community to behavior that is not commendable. For that spiritual intelligence must be considered because of the highest human intelligence that can guide humans in finding the true meaning of life. One way (approach) to change society is by strengthening spiritual intelligence. This study uses a qualitative approach which is how to get the data by doing research directly with the descriptive analysis method. Data analysis is done so that the collected data can be analyzed by analyzing all data generated from observations, interviews and documentation that have been carried out. The results showed that (1) The development of spiritual intelligence through Islamic Religious Education at SDN Gajah 1 Ngoro Jombang was carried out through the cultivation of Islamic values to students, including the values of love, value of tawadhu ', sincere values, and courageous values. The implementation of Islamic activities in schools includes daily activities, weekly activities, monthly activities and annual activities. (2) supporting factors and inhibitors of spiritual i students of SDN Gajah 1 Ngoro Jombang namely the existence of collaboration between the principal and the teacher, the existence of adequate facilities, the existence of Islamic symbols in the school, the hard work of the teacher in motivating students to be of good character, exemplary from the teacher, as well as regulations that apply at school. While the inhibiting factors are the absence of teachers of local religious content and the absence of a mosque building. Based on the analysis of research results, it is recommended to; (1) Principals, to improve the quality of teacher performance in motivating and exemplary to students and are advised to strive to improve facilities and infrastructure related to learning Islamic Education in schools. (2) Teachers, to improve the existing model of spiritual intelligence development by increasing their role as motivators by motivating and giving examples to students so that they are always noble.